EXCHANGE RATE PASS-THROUGH, IMPORT PRICES AND INFLATION UNDER STRUCTURAL BREAKS - Arintoko, Arintoko (Economic Journal of Emerging Markets, 2011)
This research estimates the exchange rate pass-through (ERPT) into import prices by applying an extension of the basic model of ERPT on Indonesia. It estimates models of cointegration and error-correction mechanism (ECM), with and without structural breaks. It uses the techniques of Zivot-Andrews and of Gregory-Hansen to test for structural breaks and cointegration with the structural breaks, respectively. The results show that with the control variables, inflation affects import prices and lower the pass-through for short term, in a condition of free floating exchange rate. In the short term, with the inclusion of structural breaks, significant inflation affects import prices and lowers the ERPT coefficient. Keywords: Exchange rate pass-through, inflation, structural breaks, cointegration, error-correction mechanism JEL classification numbers: C22, C32, E31, F41